Thyroid status and levothyroxine natrium effectiveness in patients with dilated cardiomyopathy - T. A. Abdullaev; B. U. Mardanov (Кардиоваскулярная терапия и профилактика)
Aim. To study clinical and hemodynamic parameters, in association with thyroid status (TS) markers, in patients with dilated cardiomyopathy (DCMP); to assess the effectiveness of 12-week combination of basis therapy and levothyroxine natrium (LTN) treatment. Material and methods. The study included 53 DCMP patients (39 women and 14 men), aged 22—58 years (mean age 41±2,7 years). In addition to clinical examination and hemodynamics assessment, plasma levels of triiodthyronin, thyroxin, and thyrotropin were measured in all participants. According to biochemical data, 43 patients were divided into 2 groups: Group I (n=21) with hypothyrosis (HT), and Group II (n=22) with normal TS. Group I received standard heart failure (HF) therapy and LTN. Twelve months later, the number of deaths and hospital admissions due to HF decompensation were retrospectively assessed. Results. In 39,6 % of DCMP patients, HT was observed, despite the absence of primary thyroid disease. Decreased plasma levels of thyroid hormones were associated with reduced physical stress tolerability and reduced myocardial contractility. Conclusion. The 12-week combination of basis HF therapy and LTN treatment was linked to TS normalization, improvement in clinical status and selected parameters of intracardiac hemodynamics, as well as with a significant reduction in repeat hospital admissions.